Diseño de estrategia educativa en salud sexual y reproductiva para disminuir embarazos e infecciones de transmisión sexual en adolescentes. Riobamba. 2024. - Duchicela Quispe, Anabel Jajaira (2025)
Sexual and reproductive health in adolescents is a key issue in public and educational policies due to the increase in unplanned pregnancies and sexually transmitted infections (STIs) in this age group. This problem hurts the integral development of adolescents and generates social, educational, and health consequences. In this context, the present study entitled "Design of an educational strategy in sexual and reproductive health to reduce pregnancies and sexually transmitted infections in adolescents. Riobamba, 2024" aimed to design an educational strategy based on scientific evidence, relevant and contextualized, directed to adolescents in the Riobamba canton. The research employed a quantitative approach, utilizing a non-experimental, descriptive, and retrospective design based on a systematic literature review. This review analyzed 55 scientific articles published between 2021 and 2025, selected using rigorous criteria and the CRF-QS instrument, which ensured the validity of the findings. The studies reviewed offered a comprehensive view of effective preventive strategies, highlighting the development of psychosocial skills, affective-sexual education, and access to reliable information. The results showed greater effectiveness in interventions that integrate digital technologies, a rights-based approach, work with families, and active participation of adolescents. Additionally, the findings revealed the importance of key factors, including prior knowledge, family, school environment, and safe spaces for dialogue. The study concludes with the design and validation of an educational strategy, including materials, aimed at adolescents, parents, and caregivers, focusing on self-care and informed decision-making. Its implementation can contribute significantly to preventing teenage pregnancies and STIs.